'The Hyde', Scaldeford and early medieval Wight. (2nd January 2019) - Margham, John
ABSTRACT: Upper Hyde Farm near Shanklin on the Isle of Wight was until quite recently complemented by its neighbour Lower Hyde Farm. Three landholdings named Scaldeford were recorded in 1086 totalling 1 hide. This hide farm can be reconstructed to include Upper and Lower Hyde farms, nearby Ninham Farm and the adjoining deserted site of Selbournes, with a total area of 453 acres. Other instances of shared Domesday place-names on the Isle of Wight are explored as are further instances of landholdings of 1 hide in 1066. The hide farm of Scaldeford would have formed part of a putative multiple estate centred on Brading, which in turn had been part of the regio of the wiht gara . The existence of other hide farms is postulated through two instances of 'lost' hīd place-names and the association between potentially early place-names and estates of 1 hide in 1066. The Scaldeford hide farm can be seen as a 'pioneering hide' akin to examples of hiwisc from Somerset. Earlier research based on the reconstruction of charter bounds on the Isle of Wight is compared with such hiwisc units to develop a broad correlation between the acreages of hides and the agricultural potential of the land. Appendices provide additional information about the ecological history of the Scaldeford area and the earthwork within the reconstructed hide which formed part of its internal boundary.